626 Barriers Faced by Female Surgical Trainees – A Qualitative Study. (12th October 2021) - Morgan, J; Manning, K; Wyld, L
Abstract: Aim: Today women make up 56% of medical students, yet just 12% of surgical consultants, a number that has remained static since 2013. This qualitative study aimed to explore the barriers to female success in modern surgery. Method: Semi-structured qualitative interviews were undertaken primarily with female surgical trainees to determine the barriers they face. Male trainees and Training Programme Directors were also interviewed for triangulation. Results: Nineteen interviews were performed (15 female trainees, 3 male trainees and 1 TPD) between October 2019 and March 2020. Family pressures and becoming a mother were significant barriers for women training in surgery, a barrier that did not apply to male trainees who were fathers, often resulting in women choosing to train less than full time (LTFT). Unfortunately, LTFT training presents further obstacles for female trainees. The set-up of the National training programme in surgery provides many non-gender specific barriers, chiefly moving hospital every 6 months resulting in disrupted training and long commutes. Sexism and discrimination are still common, both from colleagues and patients. Many participants perceived inherent differences between genders in communication and methods for coping with stress. Conclusions: Greater gender equality in surgery may be achieved by changes in the structure and organisation of training to reduce the tension between the professional role and the predominantly female-led role of raising children. Better equality and diversity training and awareness at all levels in surgery may help to mitigate some of the conscious and unconscious bias that still exists.